Additive-containing electrolyte for secondary battery and sodium ion secondary battery
By using specific electrolyte salts, solvents and composite additives in sodium ion secondary batteries, the problems of sodium ion secondary batteries in solvent system selection, electrolyte salt optimization and safety are solved, and higher cycle stability and Safety performance.
Patent Information
- Application Number
- CN202411787267.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
AI Technical Summary
Sodium ion secondary batteries have problems in solvent system selection, electrolyte salt optimization, safety and corrosion, which affect their performance and stability.
Using electrolyte containing composite additives, specific ingredients include sodium perchlorate or sodium hexafluorophosphate as the electrolyte salt, propylene carbonate or dimethyl carbonate as the solvent, vinyl sulfate and sodium acesulfame as the composite additives, through specific Proportion and preparation steps to prepare the electrolyte.
It significantly improves the cycle stability, charge and discharge performance and safety performance of sodium ion secondary batteries, extends the service life of the battery, and reduces the occurrence of side reactions inside the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemistry, and in particular to an electrolyte for a secondary battery containing an additive and a sodium ion secondary battery. Background Art
[0002] There are some differences between sodium ion secondary batteries and lithium ion secondary batteries:
[0003] The radius of sodium ions is significantly larger than that of lithium ions, which requires that the transmission channels in the electrolyte must be of sufficient size and appropriate shape to ensure that sodium ions can shuttle efficiently. Therefore, the electrolyte has unique requirements for the structure and arrangement of solvent molecules, as well as the types and concentrations of possible additives, so as to create a microenvironment that is conducive to sodium ion transmission.
[0004] In view of the physical and chemical properties of sodium ions, the electrolyte solvent system should have high ion solubility, low viscosity and good chemical stability, and its compatibility with the positive and negative electrode materials of the battery must also be considered. As the core component of the electrolyte, the type and concentration of electrolyte salts have a crucial impact on the conductivity, stability of the electrolyte and the overall performance of the battery. In view of the characteristics of sodium ions, it is necessary to select electrolyte salts with appropriate solubility, high ionic conductivity and good chemical stability.
[0005] Sodium-ion batteries have broad application prospects, but there are still some problems to be solved in terms of solvent system selection, electrolyte salt optimization, safety and corrosivity. Summary of the invention
[0006] The present invention provides an electrolyte for a secondary battery containing an additive, comprising:
[0007] Electrolyte salts;
[0008] A solvent selected from one or more of propylene carbonate and dimethyl carbonate;
[0009] And a composite additive comprising vinyl sulfate and sodium acesulfame, wherein the mass ratio of vinyl sulfate to sodium acesulfame is 1:0.8-1.2.
[0010] The electrolyte salt is selected from sodium perchlorate or sodium hexafluorophosphate.
[0011] Diethyl carbonate was also included as a solvent.
[0012] Ethyl methyl carbonate was also included as a solvent.
[0013] The total mass of vinyl sulfate and sodium acesulfame in the composite additive accounts for 0.5%-2% of the total mass of the electrolyte.
[0014] The electrolyte is prepared by the following steps:
[0015] a) weighing electrolyte salt and solvent;
[0016] b) mixing the electrolyte salt and the solvent and stirring until the electrolyte salt is completely dissolved;
[0017] c) adding the composite additive according to the mass ratio of vinyl sulfate to acesulfame sodium of 1:0.8-1.2, and continuing to stir to completely dissolve the additive;
[0018] d) Detect and adjust the conductivity and pH value of the electrolyte solution;
[0019] e) Filter and store the electrolyte solution.
[0020] In step d), the conductivity of the electrolyte solution is detected using a conductivity meter to ensure that it reaches above 10 mS / cm, and the pH value of the electrolyte solution is detected using a pH meter and adjusted to about pH=7.
[0021] In step e), the prepared electrolyte solution is filtered through a 0.22 μm filter membrane.
[0022] A sodium ion secondary battery, comprising:
[0023] A positive electrode, the positive electrode comprising a sodium nickel iron manganese compound NaNixFeyMnzOX as a positive electrode active material, wherein x, y, z represent the molar ratios of nickel, iron, and manganese, respectively, and O represents an oxygen element;
[0024] negative electrode;
[0025] The electrolyte comprises a specific organic solvent, an electrolyte salt and an additive, wherein the electrolyte salt is selected from sodium hexafluorophosphate (NaPF6) and / or sodium bis(fluorosulfonyl)imide (NaFSI).
[0026] The negative electrode uses hard carbon.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0028] By selecting specific solvents (such as propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc.) and electrolyte salts, and combining composite additives, an electrolyte with excellent conductivity and stability is formed. This electrolyte formula helps to improve the cycle stability, charge and discharge performance, and safety performance of sodium ion secondary batteries. In particular, the use of composite additives, through synergistic effects, effectively inhibits the occurrence of adverse side reactions in the electrolyte and extends the service life of the battery.
[0029] Sodium-ion secondary batteries use a specific positive electrode active material (sodium-nickel-iron-manganese compound NaNixFeyMnzOX), combined with an optimized electrolyte and a hard carbon negative electrode. They not only have high energy density and power density, but also exhibit good cycle stability and safety performance. DETAILED DESCRIPTION
[0030] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0031] The detailed technical scheme of the present invention is as follows:
[0032] Electrolyte preparation is the core method of using sodium ion battery additives. By selecting suitable electrolyte salts and solvents and adding appropriate additives, the performance of sodium ion batteries can be significantly improved.
[0033] 1. Selection of electrolyte salt
[0034] Electrolyte salt plays a vital role in sodium-ion batteries. It not only affects the conductivity of the electrolyte, but also affects the stability and cycle life of the battery. Common electrolyte salts include sodium perchlorate (NaClO4), sodium hexafluorophosphate (NaPF6), etc.
[0035] 1. Sodium perchlorate (NaClO4)
[0036] Sodium perchlorate is a commonly used inorganic salt with high ionic conductivity and good chemical stability. It can maintain good performance even at high temperatures and is suitable for sodium-ion batteries that need to work at high temperatures. However, the solubility of sodium perchlorate is relatively low, and an appropriate solvent needs to be selected to prepare the electrolyte solution.
[0037] 2. Sodium hexafluorophosphate (NaPF6)
[0038] Sodium hexafluorophosphate is another commonly used electrolyte salt, which has high ionic conductivity, low viscosity and good thermal stability. Sodium hexafluorophosphate has high solubility in organic solvents and can be used to prepare electrolyte solutions with high concentrations. In addition, sodium hexafluorophosphate also has good electrochemical stability and is suitable for high voltage and high energy density sodium ion batteries.
[0039] 2. Selection of solvent
[0040] Solvents play the role of dissolving electrolyte salts, transferring ions and stabilizing battery performance in electrolytes. Selecting a suitable solvent is crucial for preparing high-quality electrolyte solutions. Common solvents include propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), etc.
[0041] 1. Propylene carbonate (PC)
[0042] Propylene carbonate is a commonly used organic solvent with a high dielectric constant and low viscosity. It can effectively dissolve electrolyte salts and form stable electrolyte solutions. In addition, propylene carbonate also has good electrochemical stability and thermal stability, and is suitable for the preparation of electrolytes for sodium ion batteries.
[0043] 2. Ethylene carbonate (EC)
[0044] Ethylene carbonate is another commonly used organic solvent with a high dielectric constant, which can effectively dissolve electrolyte salts. Ethylene carbonate also has good film-forming properties and can form a stable solid electrolyte interface film (SEI film) on the surface of the battery negative electrode, thereby improving the stability and cycle life of the battery.
[0045] 3. Dimethyl carbonate (DMC)
[0046] Dimethyl carbonate is a low-viscosity organic solvent that can effectively dissolve electrolyte salts and form electrolyte solutions with good fluidity. In addition, dimethyl carbonate also has good low-temperature performance and is suitable for sodium-ion batteries that need to work at low temperatures.
[0047] It is found in the method of the present invention that unexpected technical effects can be obtained by using a solvent based on propylene carbonate in combination with specific additives.
[0048] 3. Composite Additives
[0049] As sodium-ion battery additives, diethyl sulfate (DTD) and sodium acesulfame (ACES) can reduce the anisotropic growth of sodium ions on the negative electrode surface and inhibit battery bulging. During the electrolyte preparation process, these two additives need to be added to the electrolyte solution in a specific ratio.
[0050] 1. Diethyl sulfate (DTD)
[0051] Vinyl sulfate is a commonly used film-forming additive that can form a stable SEI film on the surface of the battery negative electrode, inhibiting the decomposition of the electrolyte and the uneven deposition of sodium ions. By adding an appropriate amount of vinyl sulfate, the stability and cycle life of the battery can be improved.
[0052] 2. Acesulfame sodium (ACES)
[0053] Sodium acesulfame is a new type of sodium ion battery additive, which can effectively inhibit the anisotropic growth of sodium ions on the negative electrode surface and reduce the occurrence of battery bulging. By adding an appropriate amount of sodium acesulfame, the safety and reliability of the battery can be improved.
[0054] 4. Specific methods for preparing electrolytes
[0055] The specific method for preparing the electrolyte includes steps such as weighing, mixing, stirring and detecting the electrolyte salt and the solvent.
[0056] 1. Weighing of electrolyte salt and solvent. Calculate the mass of electrolyte salt and solvent required according to the required electrolyte solution concentration and volume. Then, use an electronic balance to accurately weigh the required electrolyte salt and solvent. During the weighing process, care should be taken to avoid cross contamination of electrolyte salt and solvent to ensure the accuracy of weighing.
[0057] 2. Mixing of electrolyte salt and solvent. Add the weighed electrolyte salt and solvent into a dry beaker respectively. Then, use a magnetic stirrer to fully mix the electrolyte salt and solvent. During the mixing process, it is necessary to maintain a moderate stirring speed to avoid excessive bubbles and foam. At the same time, observe the state of the mixed solution to ensure that the electrolyte salt is completely dissolved.
[0058] 3. Addition of composite additives
[0059] According to a specific ratio (1:0.8-1.2), diethyl sulfate (DTD) and acesulfame sodium (ACES) are added to the mixture. Then, the mixture is stirred with a magnetic stirrer to fully dissolve the additives and evenly distribute them in the electrolyte solution. In the process of adding additives, it is necessary to control the addition speed and stirring speed to avoid excessive bubbles and foam.
[0060] 4. Stirring and testing
[0061] Continue to stir the mixture until the additive is completely dissolved and evenly distributed in the electrolyte solution. Then, use a conductivity meter and a pH meter to test the conductivity and pH value of the electrolyte solution. By adjusting the ratio of the electrolyte salt and the solvent and the amount of the additive added, the conductivity and pH value of the electrolyte solution meet the predetermined requirements.
[0062] 5. Filtration and storage
[0063] Filter the prepared electrolyte solution through filter paper or filter membrane to remove impurities and particles. Then, transfer the filtered electrolyte solution to a clean container and seal it for storage. During storage, the electrolyte solution needs to be kept away from air and direct sunlight to prevent chemical changes and performance degradation.
[0064] Example 1
[0065] 1. Materials and Reagents
[0066]
[0067] 2. Preparation steps
[0068] Calculation and weighing: According to the target concentration (1 mol / L NaPF6 electrolyte), calculate the required mass of sodium hexafluorophosphate (NaPF6) and propylene carbonate (PC). Use a high-precision electronic balance to accurately weigh 10g of sodium hexafluorophosphate and 90g of propylene carbonate. Accurately weigh 0.9g of diethyl sulfate (DTD) and 0.8g of acesulfame sodium (ACES).
[0069] Mixing and stirring: Add the weighed sodium hexafluorophosphate into a dry beaker. Slowly add propylene carbonate and turn on the magnetic stirrer at 300 rpm to completely dissolve the electrolyte salt in the solvent. Observe the state of the mixture to ensure that the electrolyte salt is completely dissolved and no solid particles remain.
[0070] Adding composite additives: After the electrolyte salt is completely dissolved, add the weighed diethyl sulfate (DTD) and acesulfame sodium (ACES) to the mixture. Continue to use a magnetic stirrer to stir the mixture at a speed of 300 rpm to fully dissolve the additives and evenly distribute them in the electrolyte solution. The stirring time is set to 30 minutes to ensure that the additives are completely dissolved.
[0071] Testing and adjustment: Use a conductivity meter to test the conductivity of the electrolyte solution to ensure that it meets the predetermined requirements (above 10mS / cm). Use a pH meter to test the pH value of the electrolyte solution and adjust it to the appropriate range (pH=about 7). If the conductivity or pH value does not meet the requirements, appropriately adjust the proportion of electrolyte salts, solvents or additives, and re-stir the mixture for testing.
[0072] Filtration and storage: Filter the prepared electrolyte solution through a 0.22μm filter membrane to remove impurities and particles. Transfer the filtered electrolyte solution to a clean glass bottle with a sealed lid. Store the electrolyte in a cool, dry, well-ventilated place, avoiding direct sunlight and high temperature.
[0073] Example 2
[0074] Prepare the following materials and reagents: 10 g of sodium hexafluorophosphate (NaPF6) as an electrolyte salt to provide ionic conductivity; 50 g of propylene carbonate (PC) and 40 g of diethyl carbonate (DEC) as solvents to dissolve the electrolyte salt and transfer ions; 1.0 g of diethyl sulfate (DTD) and 0.9 g of sodium acesulfame (ACES) as additives, respectively used to form a SEI film to improve stability and inhibit the anisotropic growth of sodium ions to reduce bulging.
[0075] Use a high-precision electronic balance to accurately weigh the required mass of each component.
[0076] Add the weighed sodium hexafluorophosphate to a dry beaker. Then, slowly add the mixed solvent of propylene carbonate and diethyl carbonate, and turn on the magnetic stirrer at 300 rpm. During this process, the state of the mixed solution must be closely observed to ensure that the electrolyte salt is completely dissolved in the solvent and no solid particles remain. The stirring time can be appropriately extended according to the actual situation until the solution is completely clear and transparent.
[0077] After confirming that the electrolyte salt is completely dissolved, add the weighed vinyl sulfate and acesulfame sodium to the mixture. Continue to use the magnetic stirrer to stir the mixture at the same speed to fully dissolve the additives and evenly distribute them in the electrolyte solution. Make sure that the additives are completely dissolved and evenly dispersed.
[0078] Use a conductivity meter to test the conductivity of the electrolyte solution to ensure that it meets the predetermined requirements (above 10mS / cm). At the same time, use a pH meter to test the pH value of the electrolyte solution and adjust it to an appropriate range (pH=about 7). If the conductivity or pH value does not meet the requirements, the proportion of the electrolyte salt, solvent or additive can be appropriately adjusted, and the mixed solution can be re-stirred for testing until it meets the requirements.
[0079] Filter the prepared electrolyte solution through a 0.22μm filter membrane to remove impurities and particles. During the filtration process, care should be taken to keep the filter membrane clean and intact to avoid contamination of the electrolyte. Transfer the filtered electrolyte solution to a clean glass bottle with a sealed lid to ensure good sealing to prevent the electrolyte from being affected by air or moisture during storage. Finally, store the electrolyte in a cool, dry, well-ventilated place, avoiding direct sunlight and high temperature environment to ensure its stability and service life.
[0080] Example 3
[0081] Compared with Example 2, the materials and reagents selected are as follows:
[0082] Sodium hexafluorophosphate (NaPF6): 10 g
[0083] Propylene carbonate (PC): 30 g
[0084] Ethyl methyl carbonate (EMC): 60 g
[0085] Dithiothreitol sulfate (DTD): 0.9 g
[0086] Acesulfame sodium (ACES): 1.05 g
[0087] The preparation steps were similar to those in Example 2, but were adjusted according to the new materials and reagent amounts.
[0088] Example 4
[0089] Compared with Example 2, the materials and reagents selected are as follows:
[0090] Sodium hexafluorophosphate (NaPF6): 10 g
[0091] Propylene carbonate (PC): 40 g
[0092] Diethyl carbonate (DEC): 30 g
[0093] Ethyl methyl carbonate (EMC): 20 g
[0094] Dithiothreitol sulfate (DTD): 0.8 g
[0095] Acesulfame sodium (ACES): 0.75 g
[0096] The preparation steps were similar to those in Example 2, but were adjusted according to the new materials and reagent amounts.
[0097] Example 5
[0098] Compared with Example 2, the materials and reagents selected are as follows:
[0099] Sodium hexafluorophosphate (NaPF6): 10 g
[0100] Propylene carbonate (PC): 60 g
[0101] Diethyl carbonate (DEC): 20 g
[0102] Ethyl methyl carbonate (EMC): 10 g
[0103] Dithiothreitol sulfate (DTD): 0.7 g
[0104] Acesulfame sodium (ACES): 0.64 g
[0105] The preparation steps were similar to those in Example 2, but were adjusted according to the new materials and reagent amounts.
[0106] Example 6
[0107] Compared with Example 2, the materials and reagents selected are as follows:
[0108] Sodium hexafluorophosphate (NaPF6): 10 g
[0109] Propylene carbonate (PC): 20 g
[0110] Diethyl carbonate (DEC): 40 g
[0111] Ethyl methyl carbonate (EMC): 30 g
[0112] Dithiothreitol sulfate (DTD): 1.10 g
[0113] Acesulfame sodium (ACES): 1.20 g
[0114] The preparation steps were similar to those in Example 2, but were adjusted according to the new materials and reagent amounts.
[0115] Comparative Example 1
[0116] In this comparative example, the ratio of DTD to ACES was selected to be 1:1.8, that is, the amount of DTD was 0.5 g, and the amount of ACES was 0.9 g, and the other components were consistent with Example 2.
[0117] The materials and reagents used are as follows:
[0118] Sodium hexafluorophosphate (NaPF6): 10 g
[0119] Propylene carbonate (PC): 50 g
[0120] Diethyl carbonate (DEC): 40 g
[0121] Dithiothreitol (DTD): 0.5 g
[0122] Acesulfame sodium (ACES): 0.9 g
[0123] The electrolyte is prepared according to the preparation steps of Example 1, including calculation and weighing, mixing and initial stirring, adding composite additives, testing and adjustment, and filtering and storage.
[0124] Comparative Example 2
[0125] The ratio of DTD to ACES in this team is 1:0.5, that is, the amount of DTD is 1.2 grams, and the amount of ACES is 0.6 grams, and the other components are consistent with Example 3.
[0126] The materials and reagents used are as follows:
[0127] Sodium hexafluorophosphate (NaPF6): 10 g
[0128] Propylene carbonate (PC): 30 g
[0129] Ethyl methyl carbonate (EMC): 60 g
[0130] Dithiothreitol (DTD): 1.2 g
[0131] Acesulfame sodium (ACES): 0.6 g
[0132] The electrolyte was prepared according to the preparation steps of Example 1.
[0133] Comparative Example 3
[0134] In this comparative example, ethylene carbonate (EC) was selected to replace part of propylene carbonate, and ethyl methyl carbonate was added.
[0135] The materials and reagents used are as follows:
[0136] Sodium hexafluorophosphate (NaPF6): 10 g
[0137] Ethylene carbonate (EC): 30 g
[0138] Propylene carbonate (PC): 20 g
[0139] Ethyl methyl carbonate (EMC): 40 g
[0140] Dithiothreitol sulfate (DTD): 0.9 g
[0141] Acesulfame sodium (ACES): 0.8 g
[0142] The electrolyte was prepared according to the preparation steps of Example 1.
[0143] Comparative Example 4
[0144] In this comparative example, a combination of ethylene carbonate and ethyl methyl carbonate was selected to study the effect on the performance of the electrolyte.
[0145] The materials and reagents used are as follows:
[0146] Sodium hexafluorophosphate (NaPF6): 10 g
[0147] Ethylene carbonate (EC): 40 g
[0148] Propylene carbonate (PC): 10 g
[0149] Ethyl methyl carbonate (EMC): 40 g
[0150] Dithiothreitol sulfate (DTD): 0.7 g
[0151] Acesulfame sodium (ACES): 0.64 g
[0152] The electrolyte was prepared according to the preparation steps of Example 1.
[0153] <![CDATA[NaPF6]]> PC DEC EMC DTD(g) ACES(g) Example 1 10g 90g - - 0.90 0.80 Example 2 10g 50g 40g - 1.00 0.90 Example 3 10g 30g - 60g 0.90 1.05 Example 4 10g 40g 30g 20g 0.80 0.75 Example 5 10g 60g 20g 10g 0.70 0.64 Example 6 10g 20g 40g 30g 1.10 1.20 Comparative Example 1 10g 50g 40g - 0.50 0.90 Comparative Example 2 10g 30g - 60g 1.20 0.60 Comparative Example 3 10g 20g - 40g 0.90 0.80 Comparative Example 4 10g 10g - 40g 0.70 0.64
[0154] "-" indicates that the component is not used in this example or comparative example
[0155] Preparation of sodium ion batteries
[0156] 1. Materials and pretreatment
[0157] Positive electrode material: Sodium nickel iron manganese compound NaNixFeyMnzOX is selected as the positive electrode active material. In this compound, x, y, z represent the molar ratio of each element, and O represents the oxygen element.
[0158] Negative electrode material: Hard carbon material is used. Its stable structure and good sodium storage capacity make it the choice of negative electrode for sodium ion batteries.
[0159] Electrolyte solvent: A uniform and stable electrolyte solvent is obtained by using a specific organic solvent or combination.
[0160] Electrolyte salt: Sodium hexafluorophosphate (NaPF6) and / or sodium bis(fluorosulfonyl)imide (NaFSI) were selected as electrolyte salts, and the total concentration was set to 1 mol / L.
[0161] Additives: Existing technologies use a variety of additives, such as fluoroethylene carbonate (FEC), vinylene carbonate (VC), etc. These additives help form a solid electrolyte interface (SEI) film, which helps improve the cycle stability and safety of the battery. Lithium difluorophosphate (LiDFP) is a heterosalt additive that can build a stable SEI on the sodium metal negative electrode by optimizing the solvation structure of the gel polymer electrolyte, thereby achieving high stability of the electrolyte. Diacetic anhydride (DGA), succinic anhydride (SA), adiponitrile (ADN), N,N-diethyltrimethylsilylamine (DETMSA), N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA), etc., improve the performance of sodium ion batteries through different mechanisms, such as forming a strong interface layer, inhibiting side reactions, and increasing the ion migration rate; pentafluoro(phenoxy)cyclotriphosphazene (FPPN) can stabilize the interface between the layered oxide cathode and the hard carbon anode by forming a uniform, ultra-thin, inorganic-rich solid electrolyte interface and cathode electrolyte interface; others such as DTD (vinyl sulfate), PS (propylene sulfite), PST (1-propylene-1,3-sultone), sodium acesulfame, NaODFB (sodium difluorooxalatoborate) and TVS (tetravinylsilane).
[0162] 2. Electrolyte Preparation and Purification
[0163] Initial mixing: Add the electrolyte salt to the solvent and stir thoroughly to ensure complete dissolution.
[0164] Additive addition: According to the preset additive combination and ratio, accurately weigh and add to the electrolyte, and stir again to ensure uniform mixing.
[0165] Purification treatment: The electrolyte is strictly purified to completely remove impurities and moisture, thereby ensuring the high quality of the electrolyte.
[0166] Storage preparation: The purified electrolyte is stored in a dedicated container in preparation for subsequent battery assembly.
[0167] 3. Battery Assembly Process
[0168] Pole sheet preparation: The positive electrode material and the negative electrode material are evenly coated on the current collector, and then dried and compacted to make a pole sheet that meets the requirements.
[0169] Battery cell assembly: The prepared pole pieces are precisely assembled with key components such as diaphragms and electrolytes to ensure that no impurities and moisture enter the battery during the assembly process.
[0170] Sealing treatment: The assembled battery cells are strictly sealed to ensure that they have good sealing properties, thus making a complete sodium-ion battery.
[0171] 4. Battery performance testing and evaluation
[0172] Test environment and methods:
[0173] The prepared sodium ion battery was placed in a constant temperature box at 45°C to simulate the battery performance under high temperature working environment.
[0174] In the voltage range of 2.62-4.25V, the cycle test was carried out by 1C constant current constant voltage charging and 1C constant current discharge. Among them, the cut-off current of constant current constant voltage charging was set to 0.05C.
[0175] A 2-minute rest time is set after each charging and discharging step to simulate a short rest state in actual use.
[0176] Test indicators and calculation methods:
[0177] Battery performance: First coulombic efficiency: It is evaluated by calculating the energy conversion efficiency during the first charge and discharge process of the battery.
[0178] Capacity retention rate: The cycle stability of the battery is evaluated by comparing the discharge capacity of the battery before and after the cycle. The calculation formula is: Capacity retention rate = discharge capacity after the cycle / discharge capacity before the cycle × 100%.
[0179] Impedance growth rate: The change in internal resistance of the battery is evaluated by comparing the impedance change before and after the cycle. The calculation formula is: Impedance growth rate = (impedance after cycle - impedance before cycle) / impedance before cycle × 100%.
[0180] Swelling rate: The volume expansion degree of the battery is evaluated by comparing the volume change of the battery before and after the cycle. The calculation formula is: Swelling rate = (volume of the battery after the cycle - initial battery volume) / initial battery volume × 100%.
[0181] The electrolyte solvent (including electrolyte salt and additive) containing Examples 1-6 and Comparative Examples 1-4 is used in a sodium ion battery to form Examples 7-12 and Comparative Examples 5-8:
[0182] Example 7
[0183] Electrolyte solvent composition: refer to Example 1.
[0184] Battery performance: First coulombic efficiency: 87%; Initial internal resistance percentage: 82%
[0185] Performance after 1000 cycles: capacity retention rate: 92.90%; inflation rate: 7.30%; internal resistance growth rate: 16.20%.
[0186] Example 8
[0187] Electrolyte solvent composition: refer to Example 2.
[0188] Battery performance: First coulombic efficiency: 90%; Initial internal resistance percentage: 77%.
[0189] Performance after 1000 cycles: Capacity retention rate: 91.05%; Gas expansion rate: 7.50%; Internal resistance growth rate: 15.50%.
[0190] Example 9
[0191] Electrolyte solvent composition: refer to Example 3.
[0192] Battery performance: first coulombic efficiency: 85%; initial internal resistance percentage: 87%.
[0193] Performance after 1000 cycles: capacity retention rate: 87.50%; inflation rate: 8.10%; internal resistance growth rate: 17.04%.
[0194] Example 10
[0195] Electrolyte solvent composition: refer to Example 4.
[0196] Battery performance: first coulombic efficiency: 88%; initial internal resistance percentage: 79%.
[0197] Performance after 1000 cycles: capacity retention rate: 90.00%; inflation rate: 7.04%; internal resistance growth rate: 15.80%.
[0198] Embodiment 11
[0199] Electrolyte solvent composition: refer to Example 5.
[0200] Battery performance: first coulombic efficiency: 87%; initial internal resistance percentage: 84%.
[0201] Performance after 1000 cycles: capacity retention rate: 89.00%; inflation rate: 7.40%; internal resistance growth rate: 16.80%.
[0202] Example 12
[0203] Electrolyte solvent composition: refer to Example 6.
[0204] Battery performance: First coulombic efficiency: 90%; Initial internal resistance percentage: 76%.
[0205] Performance after 1000 cycles: capacity retention rate: 92.03%; inflation rate: 7.91%; internal resistance growth rate: 15.79%.
[0206] Comparative Example 5
[0207] Electrolyte solvent composition: refer to Comparative Example 1.
[0208] Battery performance: first coulombic efficiency: 77%; initial internal resistance percentage: 92%.
[0209] Performance after 1000 cycles: capacity retention rate: 78.00%; inflation rate: 51.04%; internal resistance growth rate: 26.51%.
[0210] Comparative Example 6
[0211] Electrolyte solvent composition: refer to Comparative Example 2.
[0212] Battery performance: first coulombic efficiency: 77%; initial internal resistance percentage: 93%.
[0213] Performance after 1000 cycles: capacity retention rate: 76.50%; inflation rate: 48.07%; internal resistance growth rate: 27.38%.
[0214] Comparative Example 7
[0215] Electrolyte solvent composition: refer to Comparative Example 3.
[0216] Battery performance: First coulombic efficiency: 78%; Initial internal resistance percentage: 91%.
[0217] Performance after 1000 cycles: capacity retention rate: 79.00%; inflation rate: 47.53%; internal resistance growth rate: 26.87%.
[0218] Comparative Example 8
[0219] Electrolyte solvent composition: refer to Comparative Example 4.
[0220] Battery performance: First coulombic efficiency: 76%; Initial internal resistance percentage: 94%.
[0221] Performance after 1000 cycles: Capacity retention rate: 75.00%; Gas expansion rate: 49.28%; Internal resistance growth rate: 27.52%.
[0222]
[0223]
[0224] The present invention proposes an innovative sodium ion battery additive solution, which reduces the anisotropic growth of sodium ions on the negative electrode surface and inhibits battery bulging by adding vinyl sulfate and sodium acesulfame mixed in a ratio of 1:0.8-1.2 to the electrolyte.
[0225] During the charging process, DTD and ACES molecules can be deposited on the negative electrode surface together with sodium ions to form a uniform coating. This coating can change the microscopic environment of the negative electrode surface, such as surface energy, charge distribution, etc., thereby affecting the deposition behavior of sodium ions. The co-deposition of DTD and ACES can significantly reduce the anisotropic growth of sodium ions on the negative electrode surface, promote isotropic growth, and thus inhibit the formation of dendrites.
[0226] Due to the presence of DTD and ACES molecules, sodium ions tend to form isotropic crystal structures rather than anisotropic dendrite structures during the deposition process. The sulfate groups of DTD and the sulfonamide groups of ACES can bind to the active sites on the negative electrode surface to form stable chemical bonds, thereby inhibiting the disordered deposition of sodium ions. At the same time, the functional groups in the molecular structures of DTD and ACES can increase the charge density on the electrode surface, reduce the diffusion energy barrier of sodium ions, and promote the uniform deposition of sodium ions.
[0227] The functional groups in the DTD and ACES molecules interact with the solvent molecules in the electrolyte to form more ion pairs, thereby improving the ion conductivity of the electrolyte. The ester groups of DTD and the sodium ions of ACES can form hydrogen bonds or ionic bonds with the solvent molecules, increase the polarization of the solvent molecules, and improve the solubility and migration rate of the ions. This improved ion conductivity helps to reduce the internal resistance of the battery and improve the performance of the battery.
[0228] When DTD and ACES are mixed in a ratio of 1:0.8-1.2, a synergistic effect is produced, further enhancing the regulation of sodium ion deposition behavior. This synergistic effect stems from the interaction between the two additive molecules and their complex interactions with sodium ions and the negative electrode surface. The functional groups in the molecular structures of DTD and ACES can complement each other to form more stable complexes and covering layers, thereby more effectively inhibiting the anisotropic growth of sodium ions.
[0229] Embodiment Performance and Verification.
[0230] The batteries with the composite additives added (Examples 1 to 6) showed higher capacity retention during the cycle. In contrast, the capacity retention of the batteries without composite additives or with improper addition ratios (Comparative Examples 1 to 4) was significantly reduced. This indicates that the addition of DTD and ACES effectively inhibited the anisotropic growth of sodium ions, reduced the formation of dendrites, and thus improved the cycle stability of the battery.
[0231] In sodium-ion batteries, the gas expansion rate is a key performance indicator, which reflects the degree of volume expansion of the battery during the cycle. Too high a gas expansion rate will not only affect the safety and stability of the battery, but may also shorten the service life of the battery. In the sodium-ion battery additive scheme proposed in the present invention, the addition of DTD and ACES inhibits the anisotropic growth of sodium ions on the negative electrode surface and promotes isotropic growth. This helps to reduce the formation of dendrites and reduce the risk of short circuits inside the battery caused by dendrites piercing the diaphragm. At the same time, uniform sodium ion deposition also helps to reduce the volume change of the battery during the cycle, thereby reducing the gas expansion rate.
[0232] The addition of DTD and ACES not only optimizes the deposition behavior of sodium ions, but also improves the stability of the electrolyte. A stable electrolyte helps reduce side reactions during battery cycling, such as gas generation, thereby reducing the gas expansion rate.
[0233] The experimental results show that the battery with the composite additives exhibits higher capacity retention and longer cycle life during the cycle process. This indicates that the addition of DTD and ACES helps to improve the cycle stability of the battery, reduce the performance degradation of the battery during the cycle process, and thus reduce the volume expansion caused by performance degradation.
[0234] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte for a secondary battery containing an additive, characterized in that: include: Electrolyte salts; A solvent selected from one or more of propylene carbonate and dimethyl carbonate; And a composite additive comprising vinyl sulfate and sodium acesulfame, wherein the mass ratio of vinyl sulfate to sodium acesulfame is 1:0.8-1.
2.
2. The electrolyte according to claim 1, characterized in that The electrolyte salt is selected from sodium perchlorate or sodium hexafluorophosphate.
3. The electrolyte according to claim 2, characterized in that Diethyl carbonate was also included as a solvent.
4. The electrolyte according to claim 2, characterized in that Ethyl methyl carbonate was also included as a solvent.
5. The electrolyte according to any one of claims 1 to 4, characterized in that The total mass of vinyl sulfate and sodium acesulfame in the composite additive accounts for 0.5%-2% of the total mass of the electrolyte.
6. The electrolyte according to any one of claims 1 to 5, characterized in that The electrolyte is prepared by the following steps: a) weighing electrolyte salt and solvent; b) mixing the electrolyte salt and the solvent and stirring until the electrolyte salt is completely dissolved; c) adding the composite additive according to the mass ratio of vinyl sulfate to acesulfame sodium of 1:0.8-1.2, and continuing to stir to completely dissolve the additive; d) Detect and adjust the conductivity and pH value of the electrolyte solution; e) Filter and store the electrolyte solution.
7. The electrolyte according to claim 6, characterized in that In step d), the conductivity of the electrolyte solution is detected using a conductivity meter to ensure that it reaches above 10 mS / cm, and the pH value of the electrolyte solution is detected using a pH meter and adjusted to about pH=7.
8. The electrolyte according to claim 6, characterized in that In step e), the prepared electrolyte solution is filtered through a 0.22 μm filter membrane.
9. A sodium ion secondary battery, characterized in that: include: A positive electrode, the positive electrode comprising a sodium nickel iron manganese compound NaNixFeyMnzOX as a positive electrode active material, wherein x, y, z represent the molar ratios of nickel, iron, and manganese, respectively, and O represents an oxygen element; negative electrode; The electrolyte comprises a specific organic solvent, an electrolyte salt and an additive, wherein the electrolyte salt is selected from sodium hexafluorophosphate (NaPF6) and / or sodium bis(fluorosulfonyl)imide (NaFSI).
10. The sodium ion secondary battery according to claim 9, characterized in that: The negative electrode uses hard carbon.